The hBN Nanoparticles as an Effective Engine Oil Additive to Enhance the Durability and Performance of a Small Diesel Engine - Abdullah, Muhammad Ilman Hakimi Chua; Abdollah, Mohd Fadzli bin; Amiruddin, Hilmi; tamaldin, noreffendy; Mat Nuri, Nur Rashid; Saleman, Abdul Rafeq (Universiti Teknologi MARA, 2017)
The aim of this study is to investigate the effectiveness of the hexagonal boron nitride (hBN) nanoparticles as additive to enhance the durability and performance of a small diesel engine. The optimum volume fraction of 70 nm hBN nanoparticles was homogeneously dispersed together with SAE 15W40 diesel engine oil. The engine performance test was performed using a single cylinder diesel engine which coupled with 20 Hp eddy current dynamometer. The results of the experimental studies demonstrated the potential of hBN as an additive for improving the engine performances, emission characteristics, fuel consumption and wear of the engine components.